Multi-faith Dynamics in Hong Kong: From Pluralism to Politicization - Chan, Kim-Kwong (The review of faith & international affairs, 2021)
Hong Kong emerged as an international, cosmopolitan city embracing both Eastern and Western culture under British colonial rule. Different religious groups lived peacefully with each other. No single religious group dominated the population and all religions were equal, an important premise for covenantal pluralism. However, after 1997 China reasserted its sovereignty over Hong Kong, politically empowered some religious groups, and de facto administered religious affairs. The recent social unrest has triggered the authority to accelerate the integration of Hong Kong into mainland China. These political changes have fundamentally transformed the religious dynamics of Hong Kong, and the basis for covenantal pluralism is diminishing.